2011
DOI: 10.1038/modpathol.2011.118
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric B-lymphoblastic leukemia with RUNX1 amplification: clinicopathologic study of eight cases

Abstract: B-lymphoblastic leukemia (a.k.a. precursor B-cell acute lymphoblastic leukemia) is a heterogeneous disease at the clinical, morphologic, immunophenotypic and genetic levels. Recurrent genetic abnormalities in B-lymphoblastic leukemia with prognostic significance are well known and specifically delineated in the WHO 2008 classification (eg hyperdiploidy, t(9;22)(q34;q11.2); BCR-ABL1, t(12;21)(p13;q22); ETV6-RUNX1). In recent years, a subgroup of B-lymphoblastic leukemia with the recurring genetic alteration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…For this assessment we need Immunophenotypic and cytogenetic prognostic markers for these patients and these markers also help us to divide cases into high and low risk patients Khan et al, (2008). In our study there were 25 (62.5%) males and 15 (37.5%) females, these results were similar to the result of Wu et al,(2010), Reichard et al, (2011) andStacy andPatrick (2015) who reported increase percentage of male than female in childhood ALL patients. The majority of patients with ALL were of B-lymphoid origin.…”
Section: Resultssupporting
confidence: 81%
“…For this assessment we need Immunophenotypic and cytogenetic prognostic markers for these patients and these markers also help us to divide cases into high and low risk patients Khan et al, (2008). In our study there were 25 (62.5%) males and 15 (37.5%) females, these results were similar to the result of Wu et al,(2010), Reichard et al, (2011) andStacy andPatrick (2015) who reported increase percentage of male than female in childhood ALL patients. The majority of patients with ALL were of B-lymphoid origin.…”
Section: Resultssupporting
confidence: 81%
“…Using an arbitrary age range for adolescents, we summarized 22 cases of B-ALL with iAMP21 for comparison. All these 22 patients had a median age of 15 years at time of diagnosis (range, 13–20) (Table 4) [8, 11, 12, 15, 16] and the male-to-female ratio was 1.75. Most patients had a low WBC count with a median of 3.4× 9 /L (range, 1–15.8).…”
Section: Discussionmentioning
confidence: 99%
“…The median age of patients is 9 years old and there is a prevalence of males. Patients with iAMP21 often show low platelet and low white blood cell counts (WBC) [58]. These patients have a relapse rate that is three times higher than other B-ALL patients are and therefore patients often require intensified therapy, particularly in older children or adolescents with B-ALL [9].…”
Section: Introductionmentioning
confidence: 99%
“…) while this gene is only 1.9% in population under study. The frequency of ETV6-RUNX1 is 17.8% and it is in agreement with the prevalence of this chimerical gene in the affluent societies like France where it is reported 19.7% in pediatric ALL population (DeBraekeleer., 2010;Reichard, 2011) Patients with t (4; 11)/MLL-AF4 are usually infants with high WBC count. They are more likely than other children with ALL to have CNS disease and to have a poor response to therapy and a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%